Studi Etnobotani Identifikasi Tanaman Berkhasiat Sebagai Pelancar ASI (Air Susu Ibu) di Kecamatan Arjasa Situbondo - Diana Lady Yunita Handoyo; Sri Nur Atiqah (Jurnal Ilmiah Wahana Pendidikan, 2022)
The use of nutritious plants as breast milk launches (Breast Milk) has been known for a long time by the people of Arjasa District of Situbondo Regency of East Java. The use of these plants has been used for a long time and hereditary from generation to generation. But over time public knowledge related to the efficacy of plants as breast milk launches began to be rare and only known by a certain group of people.his study aims to find out and document plants that are efficacious as breast milk launchers located in Arjasa. This study uses interview methods and field exploration with cruise methods. The results of the observations obtained are in the form of family and type, indonesian name, regional name, habitus, plant parts used and how to concoct. Based on the results of observations obtained the results of 15 types of medicinal plants that are used by the arjasa subdistrict community as breast milk launches. With the most habitus is trees and perdu, the part of the plant that is widely used is the leaves and the most widely used processing method is boiled as a dish or as a herbal drink.